A 10-year longitudinal analysis of the impact of demographic, lifestyle, and medical factors on semen qualities in men in a city in the midwestern region of the United States of America - Malik Scott; Anaelena Rodriguez; Orry Marciano; Rachel Nordgren; Scott D Lundy; Omer A Raheem (Asian Journal of Andrology, 2025)
This study was to survey the relationship between semen values and demographics, comorbidities, and recreational substance use in a large cohort of adult men at the University of Chicago Medical Center Department of Urology (Chicago, IL, USA). We performed an analysis from January 2013 to December 2023 of semen samples obtained from adult patients at our institution and collected their demographics, comorbid medical conditions, and recreational substance use information. Patients were divided into categories of normozoospermia, oligozoospermia, and azoospermia on the basis of the 5th version of the World Health Organization (WHO) guidelines. Data were analyzed by univariate linear and logistic regression models, after which statistically significant variables were placed into multivariable models. Azoospermia and oligozoospermia were both associated with Caucasian or Black, Indigenous, and People of Color (BIPOC) race (both P < 0.001), increasing age (P = 0.005 and P < 0.001, respectively), anemia (P < 0.001 and P = 0.02, respectively), lifetime tobacco use (both P < 0.001), lifetime alcohol use (P = 0.02 and P < 0.001, respectively), and lifetime use of at least two recreational substances (P < 0.001 and P = 0.003, respectively) in multivariable models. Oligospermia was additionally associated with benign prostatic hyperplasia (BPH; P = 0.003) in multivariable models. This study suggests that at-risk populations may benefit from additional early screening and workup for infertility.